2022
DOI: 10.1111/tbed.14466
|View full text |Cite
|
Sign up to set email alerts
|

One hundred years of African swine fever in Africa: Where have we been, where are we now, where are we going?

Abstract: One hundred years have passed since the first paper on African swine fever (ASF) was published by Montgomery in 1921. With no vaccine, ineffectiveness of prevention and control measures and lack of common interest in eradicating the disease, ASF has proven to be one of the most devastating diseases because of its significant sanitary and socioeconomic consequences. The rapid spread of the disease on the European and Asian continents and its recent appearance in the Caribbean puts all countries at great risk be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 208 publications
(343 reference statements)
1
27
0
Order By: Relevance
“…The common warthog (Phacochoerus africanus) is widespread in arid regions of sub-Saharan Africa although the exact population size is unknown, [1]; in South Africa, estimates of over 22,250 animals have been proposed [2]. Known to be an asymptomatic carrier of African swine fever virus (ASFV) [3], studies have shown that warthogs can be serologically positive for Mycobacterium bovis, Foot and Mouth Disease, Rift valley fever, influenza A and Porcine parvovirus 1 (PPV1) [4][5][6]. As pig production increases in Africa, identifying other potential pathogens in warthogs and understanding the role that this species may play in disease transmission to domestic swine is fundamental to the development of targeted disease-control strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common warthog (Phacochoerus africanus) is widespread in arid regions of sub-Saharan Africa although the exact population size is unknown, [1]; in South Africa, estimates of over 22,250 animals have been proposed [2]. Known to be an asymptomatic carrier of African swine fever virus (ASFV) [3], studies have shown that warthogs can be serologically positive for Mycobacterium bovis, Foot and Mouth Disease, Rift valley fever, influenza A and Porcine parvovirus 1 (PPV1) [4][5][6]. As pig production increases in Africa, identifying other potential pathogens in warthogs and understanding the role that this species may play in disease transmission to domestic swine is fundamental to the development of targeted disease-control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…ASFV is the sole member of the family Asfarviridae and the only known DNA arbovirus. It has had an enormous impact on swine farming in several countries in Africa, Europe and Asia due to its clinical outcome and the restrictions applied to limit its spread, which have included bans on animal movements and trade [3]. Currently, the virus has been reported in 35 African countries [7,8] where it is maintained in a sylvatic cycle involving Ornithodoros soft ticks and asymptomatically infected warthogs and bush pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Genotype III ASFV had previously been found in outbreaks of disease in pigs and in ticks at several locations only within the controlled area between 1993 and 2017 [ 34 ]. In contrast, the range of viruses detected in ticks collected within the controlled area in the present study ( Table 1 ) is typical of the variety of genotypes of ASFV known to circulate in areas where sylvatic circulation of ASFV is endemic [ 14 ].…”
Section: Discussionmentioning
confidence: 96%
“…The genotype of ASFV involved, genotype I, had been isolated decades earlier from outbreaks of disease in pigs, and from ticks in South Africa. The same genotype had long been associated with the disease in domestic pigs in countries of western Africa from where it is believed to have been accidentally introduced into Europe in 1957 and 1960 [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In South Africa, there has been widespread translocation of warthogs since 1963 to game farms and nature reserves in the south of the country, originally from a source considered to be free of ticks and virus.…”
Section: Introductionmentioning
confidence: 99%
“…All outbreaks of ASF in domestic pigs outside the control zone between 2012 and 2021 can be linked to human behavior (Janse van Rensburg et al, 2020; Penrith & Kivaria, 2022). The outbreak in Gauteng province in 2012 was traced to the illegal movement of sick pigs from the control zone to a sales yard in Mpumalanga province (Geertsma et al, 2012).…”
Section: Asf Situation In South Africamentioning
confidence: 99%